Intravenous thrombolysis for acute central retinal artery occlusion: Protocol for a systematic review and individual participant data meta-analysis of randomized controlled trials - Brian Mac Grory; Cécile Preterre; Pierre Lebranchu; Stephen James Ryan; Øystein Kalsnes Jørstad; Morten Carstens Moe; Johannes Tünnerhoff; Martin S. Spitzer; Carsten Grohmann; Oana M. Dumitrascu; Valérie Biousse; Benoit Guillon; et al. (PLoS ONE, 2026)
Importance Central retinal artery occlusion (CRAO) is a disabling subtype of acute ischemic stroke. It is not known whether intravenous (IV) thrombolysis delivered within 4.5 hours of time last known well (LKW) improves visual outcomes. Study design Systematic review and individual participant data meta-analysis. Objective The objective of this study is to determine whether IV thrombolysis improves visual outcomes among patients with acute non-arteritic CRAO when administered within 4.5 hours of time LKW compared with placebo, no IV thrombolysis, and/or anti-thrombotic therapy. Evidence review plan This study is prospectively registered through PROSPERO (#1154900). We will include randomized controlled trials (RCTs) that enroll patients with non-arteritic CRAO presenting within 4.5 hours of time LKW. We will not include non-controlled interventional studies or retrospective studies. We will search MEDLINE, Embase, the Cochrane Library, Web of Science, and the ClinicalTrials.gov registry from inception through the date of commencement of the systematic review. We will assess the risk of bias using the Cochrane Risk of Bias Tool 2.0. We will contact the corresponding author(s) of any studies identified that meet the study selection criteria. We will inspect, harmonize, and collate trial datasets. The primary end point will be attainment of a final best corrected visual acuity (BCVA) equal to or better than 20/63 (logarithm of the minimum angle of resolution [logMAR] of ≤0.5). Secondary end points will include shift analyses of key visual acuity outcome categories according to the World Health Organization (WHO) International Classification of Disease (ICD)-11, final BCVA considered as a continuous variable, final BCVA equal to or better than 20/100 (logMAR of ≤0.7), final BCVA equal to or better than 20/200 (logMAR of ≤1), a quantitative measure of visual field function (where available), global disability (modified Rankin Scale score [mRS]), and key safety end points (including symptomatic intracranial hemorrhage [sICH] and other systemic hemorrhage). We will fit a series of mixed logistic and linear regression models with trial, and trial by treatment interaction terms as random effects. To probe for sources of heterogeneity, we will pursue a series of subgroup and sensitivity analyses. Finally, a GRADE assessment will be presented. Conclusions and relevance Completion of the proposed study will permit a synopsis of the interventional literature on IV thrombolysis for CRAO, generate a pooled estimate of the treatment effect, and allow exploration of sources of heterogeneity. Such results may be of interest to healthcare professionals, guideline development bodies, policymakers, payors, and future patients with CRAO. Registration This systematic review is prospectively registered: PROSPERO #1154900.